YOLO Culture dalam Perspektif Islam: Dampak Globalisasi terhadap Perilaku Hedonisme di Kalangan Mahasiswa UIN Raden Mas Said Surakarta - Mahsuna Aulia Anggraini; Anis Maisya (Moral : Jurnal kajian Pendidikan Islam, 2025)
This study examines the influence of globalization on the YOLO (You Only Live Once) culture and hedonistic behavior among students at UIN Raden Mas Said Surakarta and offers solutions based on Islamic values. Globalization, fueled by technological and social media developments, has accelerated the spread of consumer culture. This encourages students to prioritize immediate pleasure without considering the long-term impact.The research method used was descriptive qualitative, using interviews and literature analysis. The results show that social pressure, the influence of digital trends, and easy access to a consumer lifestyle play a significant role in the rise of hedonistic behavior among students. This phenomenon indicates a shift in mindset that tends to prioritize instant gratification. From an Islamic perspective, this lifestyle is inconsistent with the principle of wasathiyah, or balance, which emphasizes simplicity, responsibility, and a meaningful life orientation. Therefore, the solutions offered include strengthening character education based on Islamic values, developing a da'wah community close to the realities of students, and providing alternative programs that can channel the energies of the younger generation toward productivity and spirituality.Through this approach, students are expected to be able to act more wisely in facing the strong currents of globalization and adopt a balanced lifestyle, not get caught up in hedonism, and still adhere to Islamic teachings